Potassium magnesium titanate, friction adjusting material, friction material composition, friction material, and friction member
By using potassium magnesium titanate with a specific composition and structure, the friction coefficient of friction materials in high-load areas is enhanced, solving the problem of insufficient friction coefficient in hybrid electric vehicles and large vehicles, reducing environmental pollution, and achieving high-efficiency friction performance and low copper emissions.
Patent Information
- Application Number
- CN202480035412.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-26
- Filing Date
- 2024-05-13
- Publication Date
- 2025-12-26
AI Technical Summary
Existing friction materials have insufficient coefficients of friction in high-load areas, especially in the braking systems of hybrid vehicles and large vehicles, resulting in insufficient braking force. At the same time, copper-containing friction materials pose a risk of environmental pollution, and titanates such as potassium hexatitanate are restricted in Europe.
By employing potassium magnesium titanate (KxMg0.4Ti1.6O4-y) with a specific composition and structure, and by controlling its Raman spectral ratio and crystal structure, the friction coefficient is enhanced and the copper content is reduced. Combined with appropriate amounts of layered and tunnel-like crystal structure titanates, a friction material composition is formed.
Improving the stability of the friction coefficient in high-load areas reduces environmental pollution, lowers the damage rate of mating materials, enhances the wear resistance and crack resistance of friction materials, and reduces the environmental impact of copper content.
Smart Images

Figure CN121219239A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to potassium magnesium titanate and friction modifiers, friction material compositions, friction materials, and friction components using potassium magnesium titanate. Background Technology
[0002] The friction materials used in braking devices such as disc brakes and drum brakes, which constitute braking systems for various vehicles and industrial equipment, require high and stable coefficients of friction, excellent wear resistance, and low damage rates to mating materials. Such friction materials can be categorized into three types: semi-metallic materials containing 30% to 60% by mass of steel fibers (such as steel or stainless steel fibers) as the fiber matrix; low-iron materials containing 10% to 30% by mass of steel fibers; and NAO (Non-Asbestos-Organic) materials that do not contain steel fibers. However, friction materials containing trace amounts of steel fibers are also classified as NAO materials.
[0003] In Japan and the United States, due to the emphasis on comfort, NAO materials, which offer a low damage rate to mating materials and an excellent balance between noise and wear resistance, are becoming mainstream. In Europe, however, low-iron materials are the mainstream choice from the perspective of maintaining the coefficient of friction during high-speed braking.
[0004] Friction material compositions (hereinafter also referred to as "friction material compositions") typically incorporate copper fibers or copper powder. One of copper's primary functions is its high thermal conductivity. Due to copper's high thermal conductivity, it allows heat generated during braking to dissipate from the friction interface, reducing wear on the friction material caused by excessive temperature rise and suppressing vibrations during braking. A second function of copper is its protection of the friction interface during high-temperature braking. Utilizing copper's ductility, a protective film extends and forms on the surface of the friction material during braking. Furthermore, it transfers to the surface of the mating material, forming an aggregated coating (hereinafter also referred to as a "transfer film"). By utilizing these aggregated coatings as protective films, wear on the friction material is reduced during high-temperature braking, and a stable coefficient of friction is achieved. However, copper-containing friction materials, due to the presence of copper in the wear debris generated during braking, potentially contribute to pollution of rivers, lakes, and oceans. Therefore, California and Washington in the United States have enacted state laws prohibiting the sale of friction materials containing more than 0.5% copper by mass and their installation in new vehicles after 2025.
[0005] Therefore, titanates have attracted attention as components other than copper that perform the function of the transfer film in NAO materials. Titanates include those with a tunnel-like crystal structure (e.g., potassium hexatitanate) and those with a layered crystal structure (e.g., potassium magnesium titanate). Depending on the application of the friction material, they can be used individually or in combination. For example, a friction material composition containing titanate and barium sulfate with an average particle size of 0.1 μm to 20 μm has been proposed (Patent Document 1).
[0006] Existing technical documents Patent documents Patent Document 1: International Publication No. 2018 / 164028 Summary of the Invention
[0007] The problem that the invention aims to solve In recent years, the braking systems of rapidly popularizing hybrid and electric vehicles have been equipped with regenerative brakes to recover frictional energy during braking. However, this mechanism is inactive when the battery is fully charged, and with the addition of batteries, vehicle weight increases, leading to an anticipated increase in the load on the brakes. Furthermore, the widespread adoption of large vehicles, such as SUVs, with their greater weight, makes it crucial that friction materials possess a higher coefficient of friction in areas subject to higher loads than before. Additionally, there is the issue of insufficient braking force for overloaded vehicles when descending steep inclines or declines in mountainous regions.
[0008] Potassium hexatitanate, with its thermally stable crystal structure, is effective as a titanate for providing a low coefficient of friction in high-load areas. However, its use is gradually being restricted, primarily in Europe, due to its potential presence of WHO fibers exceeding environmental standards (fiber particles with a long axis diameter greater than 5 μm, a short axis diameter less than 3 μm, and an aspect ratio greater than 3). On the other hand, while potassium magnesium titanate is considered a titanate free of the possibility of containing WHO fibers, its excellent wear resistance does not address the issue of a low coefficient of friction in high-load areas.
[0009] The present invention aims to provide a magnesium potassium titanate that can increase the coefficient of friction in high-load areas when used as a friction material, a friction conditioning material using the magnesium potassium titanate, a friction material composition, a friction material, and a friction component.
[0010] Technical means to solve the problem The present invention provides, as described below, a friction modulating material using the magnesium potassium titanate, a friction material composition, a friction material, and a friction component.
[0011] Item 1: A magnesium potassium titanate, wherein the magnesium potassium titanate is composed of the formula K x Mg 0.4 Ti 1.6 O4-y This indicates that, in the formula, x is 0.1 ≤ x ≤ 0.6, and y = (0.8 - x) / 2. In the Raman spectrum of the above-mentioned potassium magnesium titanate, at 100 cm⁻¹... ﹣1 ~165cm ﹣1 The peak area (Ia) at 215 cm⁻¹ ﹣1 ~325cm ﹣1 The ratio of peak area (Ib) at 785 cm⁻¹ (Ia / Ib) is above 0.03. ﹣1 ~900cm ﹣1 Peak area (Ic) at 215 cm⁻¹ ﹣1 ~325cm ﹣1 The ratio of peak area (Ib) at that point (Ic / Ib) is below 0.40.
[0012] Item 2: Potassium magnesium titanate as described in Item 1, wherein the potassium magnesium titanate is substantially free of anatase titanium dioxide.
[0013] Item 3: Potassium magnesium titanate as described in Item 1 or Item 2, wherein the aforementioned potassium magnesium titanate is in the form of plate-shaped particles.
[0014] Item 4: Potassium magnesium titanate as described in any one of items 1 to 3, wherein the average particle size of the potassium magnesium titanate is 0.1 μm to 100 μm.
[0015] Item 5: Potassium magnesium titanate as described in any one of items 1 to 4, wherein the specific surface area of the aforementioned potassium magnesium titanate is 0.1 m². 2 / g~10m 2 / g.
[0016] Item 6: Potassium magnesium titanate as described in any one of items 1 to 5, wherein the alkali metal ion dissolution rate of the above-mentioned potassium magnesium titanate is 0.01% to 15% by mass.
[0017] Item 7: A friction modulating material, wherein the friction modulating material is formed as in any one of items 1 to 6, magnesium potassium titanate.
[0018] Item 8: A friction material composition, wherein, in the friction material composition containing magnesium potassium titanate and a bonding material as described in any one of items 1 to 6, the content of the copper component relative to 100% by mass of the total mass of the above friction material composition is less than 0.5% by mass based on copper element.
[0019] Item 9: The friction material composition as described in Item 8, wherein the content of the above-mentioned magnesium potassium titanate relative to the total mass percentage of the above-mentioned friction material composition is 1% to 40% by mass.
[0020] Item 10: A friction material composition as described in Item 8 or 9, wherein it further comprises at least one of a layered crystalline titanate and a tunnel crystalline titanate.
[0021] Item 11: A friction material composition as described in any one of items 8 to 10, wherein the friction material composition is substantially free of sulfide-based solid lubricants.
[0022] Item 12: A friction material composition as described in any one of items 8 to 11, wherein the content of steel-based fibers is less than 10% by mass relative to the total mass of the above friction material composition (100% by mass).
[0023] Item 13: A friction material composition as described in any one of items 8 to 11, wherein the content of steel-based fibers relative to the total mass percentage of the above friction material composition is 10% by mass or more.
[0024] Item 14: A friction material, wherein the friction material is a molded body of the friction material composition described in any one of items 8 to 13.
[0025] Item 15: A friction member comprising the friction material described in Item 14.
[0026] Invention Effects According to the present invention, it is possible to provide a magnesium potassium titanate that can increase the coefficient of friction in high-load areas when used as a friction material, a friction conditioning material using the magnesium potassium titanate, a friction material composition, a friction material, and a friction component. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of a scanning transmission electron microscope (STEM) image of the titanate obtained in Example 1.
[0028] Figure 2 This is a schematic diagram of the Raman spectra of the titanate and potassium hexatitanate obtained in Example 1 and Comparative Example 1.
[0029] Figure 3 This is a schematic diagram showing the relationship between the number of braking cycles and the friction coefficient during attenuation in friction test 1 of the friction components obtained in Example 7 and Comparative Example 3.
[0030] Figure 4 This is a schematic diagram showing the relationship between the change in friction coefficient (μ) relative to rotor temperature and the average friction coefficient (μ) during decay in friction test 1 of the friction components obtained in Example 7, Comparative Example 3, and Reference Example 1.
[0031] Figure 5 This is a schematic diagram of a scanning transmission electron microscope (STEM) image of the titanate obtained in Comparative Example 1. Detailed Implementation
[0032] The following describes an example of a preferred embodiment of the present invention. However, the following embodiment is merely illustrative and the present invention is not limited to the following embodiment. It should be noted that in this specification, "~" is used to indicate that the values before and after it are lower and upper limits.
[0033] <1. Potassium magnesium titanate> The magnesium potassium titanate of the present invention is characterized by having the compositional formula K x Mg 0.4 Ti 1.6 O 4-y This indicates that x is 0.1 ≤ x ≤ 0.6, and y = (0.8 - x) / 2; moreover, in the Raman spectrum of potassium magnesium titanate, 100 cm⁻¹ ﹣1 ~165cm ﹣1 The peak area (Ia) at 215 cm⁻¹ ﹣1 ~325cm ﹣1 The ratio of peak area (Ib) at 785 cm⁻¹ (Ia / Ib) is above 0.03. ﹣1 ~900cm ﹣1 Peak area (Ic) at 215 cm⁻¹ ﹣1 ~325cm ﹣1 The ratio of peak area (Ib) at that point (Ic / Ib) is below 0.40.
[0034] The inventors of this invention discovered that: when using the composition formula K x Mg 0.4 Ti 1.6 O 4-y This indicates that the formula represents potassium magnesium titanate with x ≤ 0.1 ≤ x ≤ 0.6 and y = (0.8 - x) / 2, and that in the Raman spectrum of potassium magnesium titanate, at 100 cm⁻¹... ﹣1 ~165cm ﹣1 The peak area (Ia) at 215 cm⁻¹ ﹣1 ~325cm ﹣1 The ratio of peak area (Ib) at 785 cm⁻¹ (Ia / Ib) is above 0.03. ﹣1 ~900cm ﹣1 Peak area (Ic) at 215 cm⁻¹ ﹣1 ~325cm ﹣1 When potassium magnesium titanate with a peak area (Ib) ratio (Ic / Ib) below 0.40 is used as a friction material, it can increase the coefficient of friction in high-load regions.
[0035] It should be noted that, since each crystal lattice has its own unique lattice oscillation, when a laser of a specific wavelength shines on a crystal, the light with energy loss equal to the phonon energy is scattered (this is also known as Raman scattering). Raman spectroscopy is a method that uses a spectrometer to detect this and thus determine the phonon energy.
[0036] Among them, the known composition formula K is a layered crystal structure. 0.8 Mg 0.4 Ti 1.6 O4 represents the existing fibrous ferrite-type magnesium potassium titanate Raman spectrum, which can be observed at 835 cm⁻¹. ﹣1 A characteristic peak was observed nearby, therefore the peak is believed to originate from a layered crystal structure.
[0037] Additionally, the known composition of the tunnel-like crystal structure is K2Ti6O. 13 The Raman spectrum of potassium hexatitanate, as shown, can be observed at 110 cm⁻¹. ﹣1 Nearby, 140cm ﹣1 Nearby and 860cm ﹣1 Characteristic peaks were observed nearby, which are believed to originate from the tunnel-like crystal structure of potassium hexatitanate.
[0038] The magnesium potassium titanate of this invention, based on scanning transmission electron microscopy (STEM) images, shows a tunnel-like crystal structure. Furthermore, in the Raman spectrum of the magnesium potassium titanate of this invention, at 835 cm⁻¹... ﹣1 No characteristic peaks believed to originate from a layered crystal structure were observed nearby, while at 140 cm⁻¹... ﹣1 and 860cm ﹣1 Nearby, characteristic peaks believed to originate from a tunnel-like crystal structure were observed, thus the spectrum can be considered to be close to that of a tunnel-like crystal structure.
[0039] Therefore, it can be understood that although the magnesium potassium titanate of the present invention is also magnesium potassium titanate, its crystal structure does not have a layered structure, but rather has a crystal structure similar to a tunnel crystal structure (hereinafter also referred to as "pseudo-tunnel crystal structure"). Based on these points, it is clear that the magnesium potassium titanate of the present invention is a different inorganic substance from existing magnesium potassium titanate.
[0040] Because the potassium magnesium titanate of the present invention has a pseudo-tunnel crystal structure, it is believed that it can increase the coefficient of friction when used as a friction modifier in friction materials. Furthermore, the inventors speculate that the potassium magnesium titanate of the present invention has a distorted structure compared to the tunnel structure of potassium hexatitanate. Therefore, the inventors believe that when the potassium magnesium titanate of the present invention is used as a friction modifier in friction materials with fewer steel fibers, the crystal structure breaks down under high loads and chemically acts on the metal of the mating parts, which can also enhance the stability of the coefficient of friction.
[0041] In this invention, the Raman spectrum of potassium magnesium titanate can be obtained, for example, by using a Raman spectrometer at an excitation wavelength of 785 nm and a wavenumber of 100 cm⁻¹. ﹣1 ~3200cm ﹣1 Measurements were taken under conditions of 1 second exposure time and 10 scans. Furthermore, the peak area in each wavelength range can be measured by numerical integration using the Simpson integral method after removing background noise from the Raman spectrum, for example, by employing the asymmetric least squares baseline correction method (ASLS method).
[0042] In this invention, the ratio (Ia / Ib) of potassium magnesium titanate in the Raman spectrum is 0.03 or more, preferably 0.10 or more, more preferably 0.15 or more, and preferably 2.00 or less, more preferably 1.00 or less, and even more preferably 0.40 or less. By setting the ratio (Ia / Ib) to the above range, the coefficient of friction can be further increased.
[0043] In this invention, the ratio (Ic / Ib) of potassium magnesium titanate in the Raman spectrum is 0.40 or less, preferably 0.35 or less, more preferably 0.26 or less, more preferably 0.20 or more, and more preferably 0.22 or more. By setting the ratio (Ic / Ib) within the above range, the coefficient of friction can be made more stable.
[0044] The composition of the potassium magnesium titanate of the present invention is given by K x Mg 0.4 Ti 1.6 O 4-y The formula indicates that the magnesium potassium titanate in which x is 0.1≤x≤0.6 and y=(0.8-x) / 2 is preferably 0.2 or more, more preferably 0.25 or more, and preferably 0.5 or less, more preferably 0.35 or less, from the viewpoint that it is easier to form a pseudo-tunnel crystal structure.
[0045] From the viewpoint of further improving the stability of the friction coefficient, the content of anatase titanium dioxide in potassium magnesium titanate of the present invention is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, and even more preferably substantially free of anatase titanium dioxide. It should be noted that "substantially free of anatase titanium dioxide" in this specification means below the detection limit of 1.0% by mass of the XRD method described later. Furthermore, the content of anatase titanium dioxide can of course be 0% by mass.
[0046] The preferred grain size of the potassium magnesium titanate of this invention is 20 Å to 200 Å, more preferably 30 Å to 150 Å, and even more preferably 35 Å to 100 Å. When the grain size of the potassium magnesium titanate is within the above range, a more efficient and stable coefficient of friction can be achieved. The grain size can be measured using an X-ray diffraction apparatus via the Halder-Wagner method.
[0047] From the viewpoint of the operating environment, the magnesium potassium titanate of the present invention is preferably non-fibrous particles. Examples of non-fibrous particles include spherical (including shapes with several irregularities on the surface, elliptical cross-sections, etc.), columnar (including rod-shaped, cylindrical, prismatic, strip-shaped, near-cylindrical, near-strip-shaped, etc., where the overall shape is near-columnar), plate-shaped, block-shaped, shapes with multiple protrusions (amoeba-shaped, boomerang-shaped, cross-shaped, star-shaped, etc.), and irregular shapes. Among these, the magnesium potassium titanate is preferably plate-shaped. Alternatively, the magnesium potassium titanate can also be porous particles. These various particle shapes can be arbitrarily controlled by manufacturing conditions—especially raw material composition and firing conditions. Furthermore, various particle shapes can be analyzed by observation, for example, using a scanning electron microscope (SEM).
[0048] In this specification, "non-fibrous particles" refers to particles whose L / B ratio is 5 or less when the longest side of the smallest cuboid in the circumscribed cuboid (the circumscribed cuboid) is set as the major axis particle diameter L, the second longest side as the minor axis particle diameter B, and the shortest side as the thickness T (B > T). Furthermore, "having multiple protrusions" means that the projected shape on the plane has protrusions in at least two directions, forming a shape different from ordinary polygons, circles, ellipses, etc. Specifically, these protrusions refer to the portions that protrude relative to these basic shapes when a polygon, circle, ellipse, etc., is applied to a photograph (projection image) obtained using a scanning electron microscope (SEM).
[0049] The average particle size of the potassium magnesium titanate of the present invention is preferably 0.1 μm to 100 μm, more preferably 1 μm to 50 μm, and even more preferably 3 μm to 30 μm. When the average particle size of the potassium magnesium titanate is within the above range, the friction performance can be further improved after it is made into a friction material. In this specification, "average particle size" refers to the particle size at which 50% of the volume reference in the particle size distribution measured by laser diffraction is accumulated. The particle size D at which 50% of the volume reference is accumulated is... 50 It is the cumulative curve obtained by calculating the particle size distribution based on volume and setting the total volume to 100%, in which the number of particles is counted from small to large, and the corresponding particle size when the cumulative value reaches 50%.
[0050] The specific surface area of the magnesium potassium titanate of the present invention is preferably 0.1 m². 2 / g~10m 2 / g, more preferably 0.3m 2 / g~6m 2 / g, further preferably 0.4m 2 / g~5m 2 / g. When the specific surface area is within the above range, the friction performance can be further improved after it is made into a friction material. It should be noted that the specific surface area can be measured according to JIS Z8830.
[0051] The alkali metal ion dissolution rate of potassium magnesium titanate of the present invention is preferably 0.01% to 15% by mass, more preferably 0.05% to 6% by mass, and even more preferably 0.1% to 3% by mass.
[0052] Furthermore, the inventors believe that in the curing reaction of a phenolic varnish-type phenolic resin, an example of a thermosetting resin used as a friction material composition, the curing reaction is initiated by the ring-opening reaction of a curing agent (or curing accelerator), such as hexamethylenetetramine, which combines with the hydroxyl groups in the phenolic varnish-type phenolic resin. However, if alkali metal ions are present at this time, they will undergo an ion exchange reaction with the hydrogen ions in the hydroxyl groups of the phenolic varnish-type phenolic resin, which will hinder the combination of hexamethylenetetramine (curing agent (or curing accelerator)) and the phenolic varnish-type phenolic resin (thermosetting resin) (hindering curing). On the other hand, the wear and damage to the friction material due to braking causes the alkaline component from potassium magnesium titanate to dissolve on the friction surface.
[0053] Therefore, by setting the alkali metal ion dissolution rate below the aforementioned upper limit, it is possible to prevent hindrance to the curing of the thermosetting resin during the heating and pressurizing molding process, thereby further improving crack resistance under high temperature and high load conditions. Furthermore, by setting the alkali metal ion dissolution rate above the aforementioned lower limit, even when the friction material using potassium magnesium titanate of the present invention is braked and left unused for a long period, rotor rusting can be suppressed. In other words, by setting the alkali metal ion dissolution rate of potassium magnesium titanate within the aforementioned range, it is possible to simultaneously achieve higher levels of crack resistance in the friction material and suppression of rotor rusting.
[0054] It should be noted that in this specification, "alkali metal ion dissolution rate" refers to the mass ratio of alkali metal ions dissolved from the sample such as magnesium potassium titanate into water at 80°C.
[0055] In this invention, from the viewpoint of further improving the adhesion to the bonding material used in the friction material composition, a treatment layer containing a surface treatment agent can also be formed on the surface of potassium magnesium titanate. Examples of surface treatment agents include silane coupling agents and titanium coupling agents. Among these, silane coupling agents are preferred, and amino-based silane coupling agents, epoxy-based silane coupling agents, or alkyl-based silane coupling agents are more preferred. The aforementioned surface treatment agents can be used alone or in combination.
[0056] Examples of amino-based silane coupling agents include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-ethoxysilyl-N-(1,3-dimethylbutylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, and N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane.
[0057] Examples of epoxy silane coupling agents include 3-glycidoxypropyl(dimethoxy)methylsilane, 3-glycidoxypropyltrimethoxysilane, diethoxy(3-glycidoxypropyl)methylsilane, triethoxy(3-glycidoxypropyl)silane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0058] Examples of alkyl silane coupling agents include methyltrimethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, n-propyltrimethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, cyclohexylmethyldimethoxysilane, n-octyltriethoxysilane, and n-decyltrimethoxysilane.
[0059] As a method for forming a treatment layer containing a surface treatment agent on the surface of magnesium potassium titanate, known surface treatment methods can be used, such as wet methods that involve dissolving the surface treatment agent in a solvent that promotes hydrolysis (e.g., water, alcohol, or a mixture thereof) to prepare a solution, and then spraying the solution onto the magnesium potassium titanate.
[0060] When treating the surface of the above-mentioned magnesium potassium titanate with a surface treatment agent, there is no particular limitation on the amount of the surface treatment agent. In the case of a wet method, it is acceptable to use a solution of the surface treatment agent for spray treatment, such that the amount of the surface treatment agent is 0.1 to 20 parts by mass relative to 100 parts by mass of magnesium potassium titanate.
[0061] The magnesium potassium titanate of the present invention can also be a granular product formed by treating the magnesium potassium titanate with the above-described surface treatment agent or the binding material described later. The average particle size of the granular magnesium potassium titanate is preferably 100 μm to 200 μm.
[0062] (Manufacturing method of potassium magnesium titanate) The method for manufacturing potassium magnesium titanate of the present invention is not particularly limited, and it can be manufactured by, for example, by the following method.
[0063] It can be manufactured by first preparing potassium magnesium titanate (sometimes referred to as "raw material KTMO") as a raw material, then mixing the raw material KTMO with acid (acid treatment), and then calcining the compound obtained by acid treatment.
[0064] As a raw material, KTMO is preferred. 0.8 Mg 0.4 Ti 1.6 O4, K 0.7 Mg 0.4 Ti 1.6 O 3.95 Potassium magnesium titanate with an isolayered crystal structure. By using the layered crystal structure as a raw material to form a pseudo-tunnel crystal structure, excellent frictional properties can be achieved. In addition, this can also inhibit the formation of WHO fibers.
[0065] The raw material KTMO can be obtained by calcining, for example, a mixture of titanium dioxide or compounds that produce titanium dioxide upon heating (collectively referred to as "titanium compounds"), potassium oxide or compounds that produce potassium oxide upon heating (collectively referred to as "potassium compounds"), and magnesium oxide or compounds that produce magnesium oxide upon heating (collectively referred to as "magnesium compounds").
[0066] In conventional methods for manufacturing potassium magnesium titanate, potassium chloride, potassium fluoride, potassium molybdate, potassium tungstate, etc., are used as fluxes in order to generate crystals at temperatures below their melting point and to ensure that the crystals retain an euhedral structure surrounded by flat crystal planes that reflect the crystal structure during crystal growth, thus facilitating the specification of crystal orientation.
[0067] In the manufacturing process of the raw material KTMO used in this invention, the crystal growth of the raw material KTMO can be suppressed, making it easier to form a pseudo-tunnel crystal structure in subsequent processes. Therefore, from this viewpoint, the amount of flux used is preferably less than 10 parts by mass, more preferably 0 parts by mass, relative to 100 parts by mass of the combined amount of titanium compound, potassium compound, and magnesium compound. Furthermore, from the viewpoint of making it easier for potassium to dissolve from between the crystal layers of the layered crystal structure of the raw material KTMO to form the target composition and to easily form a pseudo-tunnel crystal structure, it is preferable to control the chloride ion concentration on the surface of the raw material KTMO particles or within the crystals to a certain amount. Specifically, the chloride ion dissolution rate of the raw material KTMO is preferably less than 400 ppm, more preferably less than 200 ppm.
[0068] In this specification, "chloride ion dissolution rate" refers to the mass percentage of chloride ions that dissolve from a sample such as titanate or titanium compound into water at 25°C.
[0069] As titanium compounds, low-valent titanium dioxide, hydrated titanium dioxide, and hydrated titanium dioxide can be used. Among these, titanium dioxide is preferred as the titanium compound. As the crystal system of titanium dioxide, rutile or anatase is preferred. Titanium compounds can be used alone or in combination of two or more. From the viewpoint of further reducing the chloride ion dissolution rate of the raw material KTMO, the chloride ion dissolution rate of the titanium compound is preferably below 100 ppm, more preferably below 50 ppm.
[0070] Examples of potassium compounds include potassium oxide, potassium carbonate, potassium hydroxide, and potassium nitrate. Among these, potassium carbonate or potassium hydroxide are preferred. A single potassium compound can be used, or two or more can be used in combination.
[0071] Examples of magnesium compounds include magnesium oxide, magnesium hydroxide, magnesium carbonate, and magnesium fluoride. Among these, magnesium hydroxide is preferred. A single magnesium compound can be used, or two or more compounds can be used in combination.
[0072] The mixing ratio of titanium compounds, potassium compounds, and magnesium compounds can be adjusted according to the composition of the target raw material KTMO. For example, in the manufacture of K... 0.8 Mg 0.4 Ti 1.6 When O4 is used as the raw material KTMO, the ratio can be set as Ti∶K∶Mg=1.6∶0.8∶0.4 (molar ratio).
[0073] Calcination of the raw material KTMO can be carried out using an electric furnace or similar equipment. Furthermore, the calcination process can be completed by maintaining the temperature within the range of 800℃ to 1100℃ for 1 to 24 hours. After calcination, the resulting powder is pulverized to the desired size or sieved for classification.
[0074] There are no particular restrictions on the acids used in acid treatment; any known acids can be used. Examples of acids used in acid treatment include inorganic acids such as sulfuric acid, hydrochloric acid, and nitric acid, and organic acids such as acetic acid. Two or more acids may also be used in combination as needed.
[0075] Furthermore, acid treatment can be performed by mixing acid with an aqueous slurry of the raw material KTMO. The concentration of the aqueous slurry is not particularly limited and can be appropriately selected from a wide range. Considering factors such as operability, the concentration of the aqueous slurry only needs to be between 1% and 30% by mass. Additionally, since the acid treatment involves calcination in a partially potassium-deficient crystalline state, resulting in a pseudo-tunnel crystal structure, the amount of acid mixed in the aqueous slurry relative to the interlayer element of the raw material KTMO is preferably 0.10 to 0.40 equivalents, more preferably 0.20 to 0.30 equivalents. It should be noted that after acid treatment, the solid components are separated from the aqueous slurry through processes such as filtration and centrifugation. The separated solid components can also be washed and dried as needed.
[0076] Calcination can be carried out using an electric furnace or similar means. Furthermore, from the viewpoint of both forming a pseudo-tunnel crystal structure and suppressing the crystal transformation to anatase titanium dioxide and other crystal structures, it is preferable to perform the calcination at a temperature range of 350°C to 600°C, more preferably 400°C to 550°C, and this temperature range is preferably maintained for 0.5 hours to 12 hours, more preferably 0.5 hours to 10 hours, and even more preferably 0.5 hours to 5 hours. After calcination, the resulting powder can be pulverized to the desired size or sieved for classification. Through the above operations, the potassium magnesium titanate of the present invention can be obtained.
[0077] It should be noted that, in the method for manufacturing potassium magnesium titanate of the present invention, as described above, by reducing the amount of flux used in the manufacturing process of raw material KTMO, or by reducing the chloride ion dissolution rate of raw material KTMO, and by applying heat energy to the unstable crystals of raw material KTMO that lack part of potassium through calcination, the above-mentioned ratios (Ia / Ib) and (Ic / Ib) of the obtained potassium magnesium titanate can be adjusted to the target range.
[0078] <2. Friction Material Composition> The friction material composition of the present invention is characterized in that it contains potassium magnesium titanate of the present invention and a binding material, and the content of copper component relative to 100% by mass of the total mass of the friction material composition is less than 0.5% by mass (calculated as copper element). In the above friction material composition, the potassium magnesium titanate of the present invention can be used as a friction modifier. Furthermore, the friction material composition of the present invention may further contain steel-based fibers and other materials as needed. It should be noted that, in this specification, "friction material composition" refers to a composition used as a friction material.
[0079] Since the friction material composition of the present invention contains potassium magnesium titanate as a friction modifier, it can increase the coefficient of friction in the high-load region of the friction material.
[0080] Furthermore, by ensuring that the content of the copper component, calculated as elemental copper, is less than 0.5% by mass relative to the total mass of the friction material composition, and preferably without copper components, the environmental impact can be reduced compared to existing friction material compositions. It should be noted that, in this specification, "without copper components" means that copper fibers, copper powder, and any copper-containing alloys (brass, bronze, etc.) and compounds are not used as raw materials in the friction material composition.
[0081] The friction material composition according to the present invention can achieve excellent frictional performance even when it contains no copper component or has a reduced copper component content.
[0082] (2-1 Based on the material) A bonding material is a material used to integrate the additives contained in a friction material composition and to provide strength. As a bonding material used in the friction material composition of the present invention, thermosetting resins commonly used as bonding materials in friction materials can be used, but are not particularly limited to, those intended to form a cohesive whole.
[0083] Examples of thermosetting resins include phenolic resins; elastomer-dispersed phenolic resins such as acryloyl elastomer-dispersed phenolic resins and silicone elastomer-dispersed phenolic resins; modified phenolic resins such as acryloyl-modified phenolic resins, silicone-modified phenolic resins, cashew nut oil-modified phenolic resins, epoxy-modified phenolic resins, and alkylbenzene-modified phenolic resins; formaldehyde resins; melamine resins; epoxy resins; acrylic resins; aromatic polyester resins; and urea resins. One type can be used alone, or two or more can be used in combination. From the viewpoint of further improving heat resistance, moldability, and friction properties, phenolic resins (linear phenolic resins) or modified phenolic resins are preferred as thermosetting resins. While either cresol phenolic resins or phenolic varnish-type phenolic resins can be used, phenolic varnish-type phenolic resins are preferred from the viewpoint of manufacturing stability and cost. Furthermore, phenolic varnish-type phenolic resins may contain additives such as curing agents and curing accelerators (e.g., hexamethylenetetramine) as needed.
[0084] The content of the bonding material in the friction material composition relative to 100% by mass of the total mass of the friction material composition is preferably 5% to 30% by mass, more preferably 8% to 20% by mass. By keeping the content of the bonding material within the above range, an appropriate amount of bonding material can be filled into the gaps between the mating materials, thereby achieving better frictional performance.
[0085] (2-2. Potassium magnesium titanate) The magnesium potassium titanate used in the friction material composition of this invention is the magnesium potassium titanate of this invention described above. Because it contains the magnesium potassium titanate of this invention, the coefficient of friction of the resulting friction material in high-load regions can be increased. Furthermore, it is expected to reduce the amount of fine friction dust such as PM10 and PM2.5 generated during braking.
[0086] The content of the aforementioned potassium magnesium titanate in the friction material composition relative to 100% by mass of the total mass of the friction material composition is preferably 1% to 40% by mass, more preferably 5% to 35% by mass, and even more preferably 10% to 30% by mass. By setting the content of the aforementioned potassium magnesium titanate within the above range, better friction performance can be achieved. Furthermore, when the aforementioned potassium magnesium titanate is used in combination with other titanates described later, the content of the aforementioned potassium magnesium titanate relative to 100% by mass of the total mass of the friction material composition is preferably 5% to 20% by mass.
[0087] The mass ratio of potassium magnesium titanate to the binder (potassium magnesium titanate / binding material) is preferably 0.1 to 8.0, more preferably 0.5 to 6.0, and even more preferably 1.1 to 4.0. By setting the mass ratio of potassium magnesium titanate to the binder within the above range, the forming performance of the friction material can be further improved, and a suitable transfer film can be formed.
[0088] (2-3. Steel-based fiber) In addition to the bonding material and potassium magnesium titanate of the present invention, the friction material composition of the present invention may, as needed, contain steel-based fibers used in conventional friction material compositions. Examples of steel-based fibers include steel fibers and stainless steel fibers, with steel fibers being preferred.
[0089] Examples of steel fibers include straight fibers obtained by methods such as flutter cutting, and coiled fibers obtained by cutting long fibers. Straight fibers are fibers with a straight shape. On the other hand, coiled fibers refer to shapes with curved sections, including simple arc-shaped products, wavy products, and products bent into spirals or vortices.
[0090] From the viewpoint of reducing the shedding of friction material from the friction surface and further ensuring frictional performance during high-temperature braking, coiled fibers are preferred as steel fibers. Furthermore, coiled fibers are more preferably fibers containing a portion with a radius of curvature of 100 μm or less. In this case, the adhesion to the friction material becomes stronger, further reducing the shedding of friction material from the friction surface.
[0091] From the viewpoint of further improving wear resistance at high temperatures, the average fiber length of the steel-based fibers is preferably 5 mm or less, more preferably 2.5 mm or less. Furthermore, from the viewpoint of further improving reinforcement performance, the average fiber length of the steel-based fibers is preferably 0.1 mm or more, more preferably 0.5 mm or more, and even more preferably 1.1 mm or more.
[0092] From the viewpoint of further suppressing braking vibration at high temperatures, the average fiber diameter of the steel-based fibers is preferably 300 μm or less, more preferably 100 μm or less. Furthermore, from the viewpoint of further preventing the shedding of the steel-based fibers, the average fiber diameter of the steel-based fibers is preferably 10 μm or more, more preferably 30 μm or more.
[0093] The average fiber length and average fiber diameter of steel-based fibers can be confirmed using microscopes or similar methods. For example, the average value of 30 steel-based fibers observed under a microscope can be taken.
[0094] In the case of NAO materials where the content of steel-based fiber relative to the total mass of the friction material composition is less than 10% by mass (preferably 0% by mass), the friction coefficient in the high-load region can be increased, and the stability of the friction coefficient can be further improved.
[0095] In the case of a low-iron material in which the content of steel-based fiber relative to the total mass of the friction material composition is 10% to 30% (preferably 13% to 23% by mass), the coefficient of friction in the high-load region can be increased.
[0096] When steel-based fibers are added to the friction material composition of the present invention, the mass ratio of potassium magnesium titanate to steel-based fibers (potassium magnesium titanate / steel-based fibers) is preferably 0.1 to 3.0, more preferably 0.6 to 2.5, further preferably 0.7 to 1.5, and particularly preferably 0.8 to 1.2. By setting the mass ratio of potassium magnesium titanate to steel-based fibers within the above range, the shedding of steel-based fibers can be further suppressed.
[0097] (2-4. Other materials) In addition to the bonding material and the friction modifier of the present invention, other materials commonly used in friction material compositions (fiber substrate, organic friction modifier, inorganic friction modifier, lubricant, pH modifier, filler, etc.) may be added as needed.
[0098] The content of other materials in the friction material composition relative to 100% by mass of the total mass of the friction material composition is preferably 20% to 94% by mass.
[0099] (2-4-1. Fiber substrate) Fiber-based materials are reinforcing components in friction materials. Examples of fiber-based materials include inorganic fibers, metal fibers, organic fibers, and carbon-based fibers. One type can be used alone, or two or more can be used in combination.
[0100] When the friction material composition contains a fiber matrix other than steel fiber, the content of the fiber matrix is preferably 0.1% to 40% by mass, more preferably 0.1% to 20% by mass, and more preferably 0.1% to 10% by mass relative to 100% of the total mass of the friction material composition.
[0101] Examples of inorganic fibers include glass fiber, rock wool, ceramic fiber, biodegradable ceramic fiber, biodegradable mineral fiber, biosoluble fiber (SiO2-CaO-SrO series fiber, etc.), wollastonite fiber, silicate fiber, and mineral fiber, among which rock wool is preferred.
[0102] When the friction material composition contains rock wool, its content is preferably 1% to 10% by mass, more preferably 1% to 7% by mass, relative to 100% by mass of the total mass of the friction material composition. When the rock wool content is within the above range, the coefficient of friction can be further increased under high-load braking.
[0103] As metal fibers, examples include fibers in the form of elemental or alloyed metals such as aluminum, iron, zinc, tin, titanium, nickel, magnesium, and silicon (excluding steel-based fibers), which are straight or coiled metal fibers with metal as the main component.
[0104] Examples of organic fibers include aromatic polyamide (aramid) fibers, fibrillated aramid fibers (also known as aramid pulp), acrylonitrile fibers (fibers made primarily of acrylonitrile homopolymers or copolymers), fibrillated acrylonitrile fibers, cellulose fibers, fibrillated cellulose fibers, and phenolic resin fibers.
[0105] Because the friction material is endowed with moderate water absorption, moisture in the atmosphere is easily absorbed into the friction material, and the alkaline components of titanate are easily dissolved, it is expected to achieve rust prevention effects on rotors and steel-based fibers. Therefore, the aforementioned organic fiber is preferably aramid fiber or fibrillated aramid fiber. From the viewpoint of further improving heat resistance, the aforementioned organic fiber is preferably para-aramid fiber, represented by poly(p-phenylene terephthalamide). Furthermore, from the viewpoint of further improving the formability of the friction material and further improving the retention of filler, the aforementioned organic fiber is preferably fibrillated aramid fiber. The specific surface area of the fibrillated aramid fiber is preferably 5 m² / s. 2 / g~25m 2 / g, more preferably 5m 2 / g~15m 2 / g. The fiber length of the fibrillated aramid fiber is preferably 0.5mm to 1.2mm.
[0106] When the friction material composition contains fibrillated aramid fibers, the content is preferably 1% to 10% by mass, more preferably 1% to 8% by mass, and even more preferably 1% to 6% by mass, relative to 100% by mass of the total mass of the friction material composition. As long as the content of fibrillated aramid fibers is above the lower limit mentioned above, crack resistance and abrasion resistance can be improved. Furthermore, as long as the content of fibrillated aramid fibers is below the upper limit mentioned above, the deterioration of crack resistance and abrasion resistance due to uneven distribution of fibrillated aramid fibers and other materials can be more reliably prevented.
[0107] Examples of carbon-based fibers include refractory fibers, PAN-based carbon fibers, pitch-based carbon fibers, and activated carbon fibers.
[0108] (2-4-2. Organic friction modifiers) Organic friction modifiers are added to further improve the acoustic and vibration performance, wear resistance, and other properties of friction materials. Examples of organic friction modifiers include uncured or vulcanized rubber powders such as tire rubber, acrylic rubber, isoprene rubber, NBR (nitrile butadiene rubber), SBR (styrene-butadiene rubber), chloroprene rubber, butyl rubber, and silicone rubber; cashew nut powder; rubber-coated cashew nut powder; and melamine powder. One type can be used alone, or two or more can be used in combination.
[0109] When the friction material composition contains an organic friction modifier, the content of the organic friction modifier is preferably 0.1% to 30% by mass, more preferably 0.1% to 20% by mass, and even more preferably 0.1% to 10% by mass, relative to 100% by mass of the total mass of the friction material composition.
[0110] (2-4-3. Inorganic friction modifiers) Inorganic friction modifiers (excluding the magnesium potassium titanate of this invention) are friction modifiers added to prevent the deterioration of the heat resistance of friction materials or to improve wear resistance and further increase the coefficient of friction. Examples of inorganic friction modifiers include abrasives, metal powders, and other inorganic fillers.
[0111] The abrasive material can be appropriately selected based on the material of the rotor, which serves as the mating component, to act as the abrasive and improve the coefficient of friction. The Mohs hardness of the mating component can be used as a benchmark for selection. From the viewpoint of more effectively representing the coefficient of friction brought about by the abrasive, the Mohs hardness of the abrasive is preferably 6 to 9, more preferably 6 to 8.
[0112] Examples of abrasives include silicon carbide, titanium dioxide, α-alumina, γ-alumina, silica, magnesia, zircon, zircon, zirconia, chromium oxide, iron oxide (such as magnetite), chromite, quartz, and iron sulfide. Among these, zircon or zircon is preferred. The average particle size of zircon is preferably 1 μm to 14 μm. The average particle size of zircon is preferably 0.2 μm to 2 μm.
[0113] Furthermore, as abrasives, abrasives with a larger average particle size can be used in combination with abrasives with a smaller average particle size. Specifically, abrasives with an average particle size of 0.5 μm to 15 μm can be used in combination with abrasives with an average particle size of 20 μm to 200 μm. Moreover, from the viewpoint of further reducing abrasive dust, the mass ratio of the abrasive with a smaller average particle size to the abrasive with a larger average particle size (abrasive with a smaller average particle size / abrasive with a larger average particle size) is preferably 0.1 to 10, more preferably 2 to 8. In this case, not only can the coefficient of friction be improved under load braking, but the stability of the coefficient of friction under light load braking can also be improved.
[0114] When the friction material composition contains abrasive, the content of abrasive is preferably 0.1% to 30% by mass, more preferably 5% to 25% by mass, and even more preferably 5% to 18% by mass, relative to 100% by mass of the total mass of the friction material composition.
[0115] Examples of metal powders include powders of elemental or alloyed metals such as aluminum, zinc, iron, and tin. One type can be used alone or in combination with two or more.
[0116] Other inorganic fillers include vermiculite, clay, mica, talc, dolomite, chromite, mullite, calcium silicate, and titanates other than the magnesium potassium titanate of this invention (hereinafter also referred to as "other titanates"). One of these fillers can be used alone or in combination with two or more.
[0117] Examples of other titanates include TERRACESS JSL, TERRACESS JSL-R, TERRACESS DP-R, TERRACESS DP-A and TERRACESS manufactured by Otsuka Chemical Co., Ltd. DP-AS, TXAX-MA, TXAX-A made by Kubota Co., Ltd., TOFIX-S, TOFIX-SNR and other potassium hexatitanate made by Toho Titanium Co., Ltd.; TERRACESS DSR and other sodium hexatitanate made by Otsuka Chemical Co., Ltd.; TERRACESS TF-SS, TERRACESS TF-S, TERRACESS TF-L, TERRACESS made by Otsuka Chemical Co., Ltd. Potassium octatitanate such as JP; magnesium potassium titanate such as TERRACESS PM and TERRACESS PS manufactured by Otsuka Chemical Co., Ltd.; lithium potassium titanate such as TERRACESS L, TERRACESS L-SS and TERRACESS JSM-M manufactured by Otsuka Chemical Co., Ltd. Other titanates are preferably sodium hexatitanate and potassium octatitanate with tunnel-like crystal structures, and potassium magnesium titanate and potassium lithium titanate with layered crystal structures, more preferably potassium magnesium titanate with layered crystal structures. It should be noted that, as other titanates, titanates with tunnel-like crystal structures and titanates with layered crystal structures can be used individually or in combination.
[0118] When other titanates are contained in the friction material composition, from the viewpoint that the coefficient of friction in the high-load area can be further increased when using the friction material, the mass ratio of other titanates to the magnesium potassium titanate of the present invention (other titanates / magnesium potassium titanate of the present invention) is preferably 0.1 to 3, more preferably 0.1 to 0.8.
[0119] (2-4-4. Lubricating materials) As a lubricating material, a solid lubricating material is preferred, such as carbon-based solid lubricating materials, sulfide-based solid lubricating materials, and polytetrafluoroethylene (PTFE). One of these materials can be used alone or in combination. The lubricating material is preferably selected from one or more of carbon-based solid lubricating materials and sulfide-based solid lubricating materials. From the viewpoint of further reducing harm to the human body, carbon-based solid lubricating materials are more preferred.
[0120] When the friction material composition contains a lubricating material, the content of the lubricating material is preferably 0.1% to 20% by mass, more preferably 1% to 10% by mass, and even more preferably 1% to 5% by mass, relative to 100% by mass of the total mass of the friction material composition.
[0121] Examples of carbon-based solid lubricants include synthetic or natural graphite, flake graphite, phosphate-coated graphite, carbon black, petroleum coke, coal coke, activated carbon, and elastic graphitized carbon materials. From the viewpoint of providing more reliable thermal conductivity, synthetic or natural graphite is preferred. When a carbon-based solid lubricant is included, its content relative to 100% by mass of the total mass of the friction material composition is preferably 0.1% by mass or more, more preferably 1% by mass or more, further preferably 2% by mass or more, and preferably less than 15% by mass, more preferably less than 10% by mass, and further preferably less than 8% by mass. When the content of the carbon-based solid lubricant is above or below the aforementioned lower limit, the wear of the friction material at high temperatures can be further improved. Furthermore, when the content of the carbon-based solid lubricant is below or below the aforementioned upper limit, it is easier to suppress the decrease in the coefficient of friction.
[0122] The average particle size of the carbon-based solid lubricant is preferably, but not particularly limited to, 10 μm to 1000 μm. The carbon-based solid lubricant can be used alone or in combination of two or more particles with different average particle sizes. When the average particle size of the carbon-based solid lubricant is above the lower limit mentioned above, it is easier to suppress excessive increases in thermal conductivity when used as a friction material, and it is also easier to suppress the occurrence of air resistance caused by frictional heat conduction to the backing plate side. Furthermore, when the average particle size of the carbon-based solid lubricant is below the upper limit mentioned above, it is easier to increase the thermal conductivity, promote the curing of the bonding material during the friction material forming process, and improve the strength of the friction material.
[0123] Examples of sulfide-based solid lubricants include antimony trisulfide, molybdenum disulfide, tin sulfide, iron sulfide, zinc sulfide, bismuth sulfide, and tungsten disulfide. From the viewpoint of further reducing harm to human health, tin sulfide or molybdenum disulfide is preferred. When containing sulfide-based solid lubricants, the content is preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more, and preferably less than 15% by mass, more preferably less than 10% by mass, and even more preferably less than 8% by mass. When the content of sulfide-based solid lubricants is above the aforementioned lower limit, rotor wear can be more easily suppressed. Furthermore, when the content of sulfide-based solid lubricants is below or below the aforementioned upper limit, the decrease in the coefficient of friction can be more easily suppressed.
[0124] The friction material composition of the present invention preferably contains substantially no sulfide-based solid lubricating materials such as metal sulfides. "Substantially free of sulfide-based solid lubricating materials" means that the sulfide-based solid lubricating materials are not intentionally added to the friction material composition, but rather that the friction material composition contains no sulfide-based solid lubricating materials except in cases where they are present as trace impurities. The content of sulfide-based solid lubricating materials relative to 100% by mass of the friction material composition is particularly preferably less than 0.1% by mass, more preferably completely free of sulfide-based solid lubricating materials. When substantially free of sulfide-based solid lubricating materials, the harm to human health is lower, and rust prevention of the rotor is expected.
[0125] The friction material composition of the present invention contains magnesium potassium titanate, steel-based fiber, carbon-based solid lubricant and bonding material of the present invention, wherein the content of copper component relative to 100% by mass of the total mass of the friction material composition is less than 0.5% by mass based on copper element, and preferably substantially free of sulfide-based solid lubricant.
[0126] In the friction material composition of the present invention containing potassium magnesium titanate, steel-based fibers, carbon-based solid lubricant, and bonding material, the content of sulfide-based solid lubricant relative to 100% by mass of the friction material composition is preferably less than 0.1% by mass, more preferably the friction material composition contains no sulfide-based solid lubricant at all. The content of steel-based fibers relative to 100% by mass of the friction material composition is preferably 10% to 30% by mass, more preferably 13% to 23% by mass. Furthermore, the mass ratio of potassium magnesium titanate to carbon-based solid lubricant (potassium magnesium titanate / carbon-based solid lubricant of the present invention) is preferably 2.0 to 6.0, more preferably 3.5 to 5.5, and even more preferably 3.5 to 5.0. By setting each component within the above ranges, a friction material can be formed that not only has low environmental and human health hazards but also contains steel-based fibers with a higher coefficient of friction in high-load areas and generates less fine wear dust such as PM10 and PM2.5 during braking.
[0127] (2-4-5. pH adjustment materials) Examples of pH adjusting materials include inorganic bases such as calcium hydroxide (quicklime), sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, trisodium phosphate, disodium hydrogen phosphate, tripotassium phosphate, and dipotassium hydrogen phosphate, as well as organic bases such as imidazole, histidine, and hexamethylenediamine. From the viewpoint of cost and hygroscopicity, inorganic bases are preferred as pH adjusting materials. One type can be used alone, or two or more can be used in combination. pH adjusting materials can also be used to prevent rust adhesion between the friction material and the mating material (rotor).
[0128] When the friction material composition contains a pH adjusting material, the content of the pH adjusting material is preferably 0.1% to 8% by mass relative to 100% of the total mass of the friction material composition.
[0129] (2-4-6. Packing) Barium sulfate and calcium carbonate are examples of fillers. Barium sulfate is preferred. It can be used alone or in combination with two or more other fillers.
[0130] Barium sulfate comes in two forms: washed barium sulfate (barite powder), obtained by crushing a mineral called barite, removing iron, washing, and rinsing; and artificially synthesized precipitated barium sulfate. Precipitated barium sulfate can be synthesized by controlling the particle size under controlled conditions, producing fine barium sulfate with a low content of coarse particles. From the viewpoint of further reducing impurities and achieving a more uniform particle size distribution in barium sulfate, precipitated barium sulfate is preferred.
[0131] (2-5. Method for manufacturing friction material composition) The friction material composition of the present invention can be manufactured by (1) mixing the components using mixing equipment such as a LOEDIGE mixing device (“LOEDIGE” is a registered trademark), a pressure kneader, or an EIRICH mixing device (“EIRICH” is a registered trademark); (2) preparing granulated products of the desired components and mixing other components using mixing equipment such as a LOEDIGE mixing device, a pressure kneader, or an EIRICH mixing device as needed.
[0132] The content of each component in the friction material composition of the present invention can be appropriately selected according to the desired friction performance, and can be manufactured by the above-described manufacturing method.
[0133] Alternatively, the friction material composition of the present invention can also be prepared by producing a masterbatch containing a high concentration of specific components, and then adding thermosetting resins or the like to the masterbatch and mixing them together.
[0134] <3. Friction Materials and Friction Components> In this invention, the above-mentioned friction material composition is pre-formed at room temperature (20°C), and the resulting pre-formed body is heated and pressurized (forming pressure 10MPa~40MPa, forming temperature 150°C~200°C). As needed, the resulting formed body is heat-treated in a heating furnace (150°C~220°C, held for 1 hour~12 hours), and then the formed body is machined and ground, thereby manufacturing a friction material with a set shape.
[0135] The friction material of the present invention can be used as a friction member formed with the friction material as a friction surface. Examples of friction members that can be formed using the friction material include (1) a structure formed solely of the friction material, and (2) a structure of the friction material of the present invention having a substrate such as a backing and a friction surface provided on the substrate.
[0136] The substrate is the part used to further improve the mechanical strength of the friction component. Examples of materials that can be used as the substrate include metals such as iron and stainless steel, and fiber-reinforced resins such as glass fiber reinforced resin and carbon fiber reinforced resin.
[0137] Friction materials typically contain numerous tiny pores. These pores not only serve as channels for the escape of decomposition products (gaseous or liquid substances) at high temperatures, preventing a decrease in frictional performance, but also reduce the rigidity of the friction material to improve damping, thereby preventing abnormal noise. In typical friction materials, the material ratio and molding conditions are managed to achieve a porosity preferably of 5%–30%, more preferably 10%–25%.
[0138] Since the friction member of the present invention is composed of the friction material composition of the present invention described above, excellent frictional performance can be obtained even when the copper component is absent or the copper component content is reduced. Therefore, the friction member of the present invention can be applied to a complete braking system of disc brake shoes, brake pads, clutch pads, etc., constituting braking devices of various vehicles and industrial equipment, and is particularly suitable as a friction member for regenerative braking.
[0139] Example The present invention will now be described in more detail based on specific embodiments.
[0140] However, the present invention is not limited to the following embodiments in any way, and may be implemented with appropriate modifications without changing its essence.
[0141] <Manufacturing of Titanates> (Comparative Example 1: Titanate A) A raw material mixture was prepared by mixing 496.9 g of anatase titanium dioxide (chloride ion leaching rate: 20 ppm), 213.7 g of potassium carbonate, and 89.4 g of magnesium hydroxide using conventional methods. This mixture was then fed into a vibratory mill and ground for 30 minutes at a vibration frequency of 1200 cpm and an amplitude of 6.0 mm. 48 ml of water was added to the grinding mixture, and 15 g of the mixture was shaped into granules using a hydraulic press under a pressure of 10 MPa. These granules were then calcined in an electric furnace at 1000°C for 4 hours and allowed to cool naturally. The calcined product was then pulverized and passed through a 20-mesh sieve to obtain the target titanate A.
[0142] The chemical composition, crystal structure, grain size, average particle size, specific surface area, particle shape, alkali metal ion dissolution rate, and chloride ion dissolution rate of the obtained titanate A are shown in Table 1.
[0143] (Comparative Example 2: Titanate B) A 20% by mass aqueous slurry of titanate A prepared in Comparative Example 1 was mixed with sulfuric acid in an amount of potassium equivalent relative to potassium magnesium titanate, and stirred at room temperature (20°C) for 2 hours. The filter cake (solid component) obtained by filtration and washing with deionized water was dried at 110°C for 12 hours, calcined in an electric furnace at 300°C for 1 hour, and then allowed to cool naturally. The calcined product was passed through a 20-mesh sieve to obtain the target titanate B.
[0144] The chemical composition, crystal structure, grain size, average particle size, specific surface area, particle shape, alkali metal ion dissolution rate, and chloride ion dissolution rate of the obtained titanate B are shown in Table 1.
[0145] (Example 1: Titanate 1) A 20% by mass aqueous slurry of titanate A prepared in Comparative Example 1 was mixed with sulfuric acid in an amount of potassium equivalent relative to potassium magnesium titanate, and stirred at room temperature (20°C) for 2 hours. The filter cake (solid component) obtained by filtration and washing with deionized water was dried at 110°C for 12 hours, calcined in an electric furnace at 500°C for 1 hour, and then naturally cooled. The calcined product was passed through a 20-mesh sieve to obtain the target titanate 1.
[0146] The chemical composition, crystal structure, grain size, average particle size, specific surface area, particle shape, alkali metal ion dissolution rate, and chloride ion dissolution rate of the obtained titanate 1 are shown in Table 1.
[0147] (Example 2: Titanate 2) A 20% by mass aqueous slurry of titanate A prepared in Comparative Example 1 was mixed with sulfuric acid in an amount of potassium equivalent relative to potassium magnesium titanate, and stirred at room temperature (20°C) for 2 hours. The filter cake (solid component) obtained by filtration and washing with deionized water was dried at 110°C for 12 hours, calcined in an electric furnace at 500°C for 12 hours, and then allowed to cool naturally. The calcined product was passed through a 20-mesh sieve to obtain the target titanate 2.
[0148] The chemical composition, crystal structure, grain size, average particle size, specific surface area, particle shape, alkali metal ion dissolution rate, and chloride ion dissolution rate of the obtained titanate 2 are shown in Table 1.
[0149] (Example 3: Titanate 3) A 20% by mass aqueous slurry of titanate A prepared in Comparative Example 1 was mixed with sulfuric acid in an amount of potassium equivalent relative to potassium magnesium titanate, and stirred at room temperature (20°C) for 2 hours. The filter cake (solid component) obtained by filtration and washing with deionized water was dried at 110°C for 12 hours, calcined in an electric furnace at 500°C for 1 hour, and then naturally cooled. The calcined product was passed through a 20-mesh sieve to obtain the target titanate 3.
[0150] The chemical composition, crystal structure, grain size, average particle size, specific surface area, particle shape, alkali metal ion dissolution rate, and chloride ion dissolution rate of the obtained titanate 3 are shown in Table 1.
[0151] (Example 4: Titanate 4) A 20% by mass aqueous slurry of titanate A prepared in Comparative Example 1 was mixed with sulfuric acid in an amount of potassium equivalent relative to potassium magnesium titanate, and stirred at room temperature (20°C) for 2 hours. The filter cake (solid component) obtained by filtration and washing with deionized water was dried at 110°C for 12 hours, calcined in an electric furnace at 600°C for 1 hour, and then allowed to cool naturally. The calcined product was passed through a 20-mesh sieve to obtain the target titanate 4.
[0152] The chemical composition, crystal structure, grain size, average particle size, specific surface area, particle shape, alkali metal ion dissolution rate, and chloride ion dissolution rate of the obtained titanate 4 are shown in Table 1.
[0153] (Example 5: Titanate 5) A 20% by mass aqueous slurry of titanate A prepared in Comparative Example 1 was mixed with sulfuric acid in an amount of potassium equivalent relative to potassium magnesium titanate, and stirred at room temperature (20°C) for 2 hours. The filter cake (solid component) obtained by filtration and washing with deionized water was dried at 110°C for 12 hours, calcined in an electric furnace at 500°C for 1 hour, and then naturally cooled. The calcined product was passed through a 20-mesh sieve to obtain the target titanate 5.
[0154] The chemical composition, crystal structure, grain size, average particle size, specific surface area, particle shape, alkali metal ion dissolution rate, and chloride ion dissolution rate of the obtained titanate 5 are shown in Table 1.
[0155] (Example 6: Titanate 6) A 20% by mass aqueous slurry of titanate A prepared in Comparative Example 1 was mixed with sulfuric acid in an amount of potassium equivalent relative to potassium magnesium titanate, and stirred at room temperature (20°C) for 2 hours. The filter cake (solid component) obtained by filtration and washing with deionized water was dried at 110°C for 12 hours, calcined in an electric furnace at 500°C for 1 hour, and then allowed to cool naturally. The calcined product was passed through a 20-mesh sieve to obtain the target titanate 6.
[0156] The chemical composition, crystal structure, grain size, average particle size, specific surface area, particle shape, alkali metal ion dissolution rate, and chloride ion dissolution rate of the obtained titanate 6 are shown in Table 1.
[0157] <Titaniumate Property Measurement> The physical properties of titanates 1 to 6, titanate A, and titanate B were measured as described below, and the results are shown in Table 1.
[0158] (Chemical composition) Confirmed using an ICP-AES analysis apparatus (SII Nanotechnology, model "SPS5100").
[0159] (Crystal structure) The findings were confirmed using scanning transmission electron microscopy (STEM, JEOL Ltd., model "JEM-ARM200F") and Raman spectroscopy (METTLER TOLEDO Ltd., model "React Raman 785"). It should be noted that the STEM observations were performed after the TEM sample was prepared using an argon-ion chipper. Furthermore, the Raman spectroscopy measurements were conducted at an excitation wavelength of 785 nm and a wavenumber of 100 cm⁻¹. ﹣1 ~3200cm ﹣1 The procedure was performed under conditions of 1 second exposure time and 10 scans. Specifically, the crystal structure was confirmed as described below.
[0160] Figure 1 This is a schematic diagram of a scanning transmission electron microscope (STEM) image of titanate 1 obtained in Example 1. Figure 5 This is a schematic diagram of a scanning transmission electron microscope (STEM) image of titanate A obtained in Comparative Example 1.
[0161] like Figure 1 As shown, titanate 1 obtained in Example 1 has a structure close to a tunnel-like crystal structure. Furthermore, titanates 2 to 6 obtained in Examples 2 to 6 also have structures close to a tunnel-like crystal structure. On the other hand, as... Figure 5As shown, titanate A obtained in Comparative Example 1 has a layered crystal structure. Titanate B obtained in Comparative Example 2 also has a layered crystal structure.
[0162] Figure 2 The images show the Raman spectra of the titanate and potassium hexatitanate obtained in Example 1 and Comparative Example 1.
[0163] like Figure 2 As shown, in the case of titanate 1 obtained in Example 1, at 835 cm ﹣1 The characteristic peaks, thought to originate from the layered crystal structure, exhibited by titanate A of Comparative Example 1 were not observed nearby. On the other hand, titanate 1 obtained in Example 1 showed a peak at 140 cm⁻¹. ﹣1 and 860cm ﹣1 Characteristic peaks, believed to originate from the tunnel-like crystal structure of potassium hexatitanate, were observed nearby. Therefore, it can be considered that the spectrum of titanate 1 obtained in Example 1 is close to that of potassium hexatitanate.
[0164] Thus, based on scanning transmission electron microscopy (STEM) images and Raman spectroscopy, it can be confirmed that titanate 1 obtained in Example 1 has a pseudo-tunneling crystal structure, which is a crystal structure close to a tunneling crystal structure. Similarly, it can be confirmed that titanates 2 to 6 obtained in Examples 2 to 6 also have pseudo-tunneling crystal structures.
[0165] Furthermore, based on the Raman spectra of titanates 1–6, titanate A, and titanate B, the 100 cm⁻¹ value can be determined. ﹣1 ~165cm ﹣1 The peak area (Ia) at 215 cm⁻¹ ﹣1 ~325cm ﹣1 The ratio of peak area (Ib) at 785 cm⁻¹ (Ia / Ib) and the peak area (Ib) at 785 cm⁻¹ ﹣1 ~900cm ﹣1 Peak area (Ic) at 215 cm⁻¹ ﹣1 ~325cm ﹣1 The ratio of the peak area (Ib) at that point (Ic / Ib).
[0166] It should be noted that when measuring the peak area in each wavelength range, the background noise of the Raman spectrum was removed by using the asymmetric least squares baseline correction method (ASLS method), and then numerical integration was performed using the Simpson integral method to obtain the result.
[0167] (Grain size) To determine the grain size, X-ray diffraction measurements were performed using wide-angle X-ray diffraction. CuKα rays (wavelength 1.5418 Å) were used as the X-ray source. A Rigaku Corporation "UltimalV" X-ray diffraction apparatus was used. X-ray diffraction measurements were performed within a 2θ range of 5° to 60°, and the grain size was calculated using the Halder-Wagner method.
[0168] (Average particle size) The particle size distribution was measured using a laser diffraction particle size distribution measuring device (manufactured by Shimadzu Corporation, product model "SALD-2100"). The particle size at which the volume reference in the obtained particle size distribution is accumulated to 50% was taken as the average particle size (μm).
[0169] (Specific surface area) The measurements were performed using an automatic specific surface area measuring device (manufactured by Micromeritics, product model "TriStarII3020").
[0170] (Particle shape) It was confirmed using a field emission scanning electron microscope (manufactured by Hitachi High Technology Co., Ltd., product model "S-4800").
[0171] (Alkali metal ion dissolution rate) The mass (X) g of the sample was measured, and then the sample was added to ultrapure water to prepare a 1% (w / w) slurry. After stirring at 80°C for 4 hours, the solid components were removed using a 0.2 μm membrane filter to obtain the extract. The mass (Y) g of alkali metal ions in the obtained extract was measured using an ion chromatograph (Dionex, product model "ICS-1100"). Then, using the above mass (X) g and (Y) g values, the alkali metal ion dissolution rate (w / w) was calculated based on the formula [(Y) / (X)] × 100.
[0172] (Chloride ion dissolution rate) The mass (X) g of the sample was measured, and then the sample was added to ultrapure water to prepare a 1% (w / w) slurry. After stirring at 25°C for 10 minutes, the solid component was removed using a 0.2 μm membrane filter to obtain the extract. The mass (Y) g of chloride ions in the obtained extract was measured using an ion chromatograph (Dionex, product model "ICS-1100"). Then, using the above mass (X) g and (Y) g values, the slurry was calculated based on the formula [(Y) / (X)] × 10⁻¹⁰. 6 The chloride ion dissolution rate (ppm) was calculated.
[0173] [Table 1] As shown in Table 1, titanates 1 to 6 obtained in Examples 1 to 6 have pseudo-tunneling crystal structures, with Raman spectra showing Ia / Ib ratios of 0.03 or higher and Ic / Ib ratios of 0.40 or lower. On the other hand, titanates A and B obtained in Comparative Examples 1 and 2 have layered crystal structures, with Raman spectra showing Ia / Ib ratios of less than 0.03 and Ic / Ib ratios of greater than 0.40.
[0174] Manufacturing of Friction Components The friction components were manufactured using titanates 1 to 6, titanate A, and the following materials.
[0175] (Based on the material) Thermosetting resin: Phenolic resin powder of varnish type containing hexamethylenetetramine (Other titanates) Titanate C: Potassium hexatitanate, columnar particles, average long axis diameter 65 μm, average short axis diameter 13 μm Titanate D: Sodium hexatitanate, porous spherical particles with an average particle size of 21.2 μm, manufactured by Otsuka Chemical Co., Ltd. (trade name: TERRACESS DSR). Titanate E: Potassium hexatitanate, porous spherical particles with an average particle size of 60.1 μm, manufactured by Otsuka Chemical Co., Ltd. (trade name: TERRACESS DP-AS). Titanate F: Potassium hexatitanate, columnar particles, average particle size 36 μm, manufactured by Otsuka Chemical Co., Ltd. (trade name: TERRACESS JSL). (Steel-based fiber) Steel fiber: Manufactured by Bonstar Sales Co., Ltd., product name "Cut Wool BS-1V", coiled fiber, average fiber length (cutting length) 1.5mm, average fiber diameter 50μm (Other materials) Rock wool: Average fiber length 125μm, maximum slag ball content (above 125μm) 5.0% Aramid fiber: Protofibrillated para-aramid fiber (aramid pulp), fiber length 0.89 mm, specific surface area 9.8 m². 2 / g Cashew nut powder: average particle size 200μm Zirconium silicate 1: Zirconium silicate powder, average particle size 1.1 μm, Mohs hardness 7.5. Zirconium silicate 2: Zirconium silicate powder, average particle size 1.5 μm, Mohs hardness 7.5. Iron oxide: average particle size 0.3 μm, Mohs hardness 6 Alumina: α-alumina, average particle size 57 μm, Mohs hardness 9 Mica: Natural mica, average particle size 180μm Graphite: Synthetic graphite, average particle size 730 μm Antimony trisulfide: Average particle size 1.5 μm Tin sulfide: Tin sulfide (II), average particle size 7 μm Quicklime: Average particle size 0.2μm Barium sulfate 1: Precipitated barium sulfate powder, average particle size 1.6 μm Barium sulfate 2: Washed barium sulfate powder, average particle size 24μm (Examples 7-17, Comparative Example 3 and Reference Example 1: Friction Component (NAO Component)) The materials were mixed according to the proportions listed in Tables 2 and 3 using an EIRICH mixing apparatus for 3 minutes. The resulting mixture was then pressurized at 15 MPa for 5 seconds at room temperature (20°C) to form a preform. This preform was then inserted into the cavity of a thermoforming mold heated to 150°C, with a backing plate (material: steel) placed on top, and pressurized at 10 MPa to 40 MPa for 300 seconds to achieve a porosity of 15%. Five venting processes were performed between 5 and 70 seconds from the start of pressurization. The resulting preform was then placed in a constant-temperature drying apparatus heated to 220°C for 2 hours for complete curing, thus obtaining the friction component (NAO component).
[0176] (Examples 18-21, Comparative Examples 4-7: Friction Components (Low-Iron Components)) The materials were mixed according to the proportions listed in Tables 5 and 6, and then mixed for 3 minutes using an EIRICH mixing apparatus. The resulting mixture was added to the cavity of a thermoforming mold heated to 150°C, with a backing plate (material: steel) placed on top, and pressurized at 15 MPa to 40 MPa for 240 seconds to achieve a porosity of 15% in the molded body. The resulting molded body was then placed in a constant-temperature drying apparatus heated to 210°C and kept for 2 hours for complete curing, thus obtaining a friction component (low-iron component).
[0177] <Evaluation of Friction Components> The Rockwell hardness and degradation tests of the friction components prepared as described above were evaluated as follows.
[0178] (Rockwell hardness) The Rockwell hardness of the friction component surface was measured according to JIS D4421. The hardness scale used was the S scale.
[0179] (Friction Test 1) The surfaces of the friction components (friction surfaces) were ground to 1.0 mm, and brake performance was tested according to JASO C406. The only difference was that the first fade test condition was changed to a high-load speed of 160 km / h for the brake performance test. It should be noted that a cast iron rotor belonging to ASTM standard number A48 / A48M was used.
[0180] Figure 3 This is a schematic diagram showing the relationship between the number of braking cycles and the friction coefficient during the decay of the friction components obtained in Example 7 and Comparative Example 3 during friction test 1.
[0181] according to Figure 3 It can be seen that, compared with comparative example 3 which uses a layered crystal structure, the magnesium potassium titanate in Example 7, which uses a pseudo-tunnel crystal structure, has a larger coefficient of friction in the high-load region and better stability of the coefficient of friction.
[0182] Figure 4 This is a graph showing the relationship between the change in friction coefficient (μ) relative to rotor temperature and the average friction coefficient (μ) during fading in the membrane material test 1 of the friction components obtained in Example 7, Comparative Example 3, and Reference Example 1. It should be noted that the average friction coefficient (μ) during fading is obtained based on the average value (average μ) of 10 braking cycles in the first fading test results.
[0183] according to Figure 4 It can be seen that Example 7, which uses potassium magnesium titanate with a pseudo-tunnel crystal structure, can also achieve a friction coefficient of equal or higher than that of Reference Example 1, which uses potassium hexatitanate with a layered crystal structure, and the stability of the friction coefficient is also improved.
[0184] It should be noted that the average value (average μ) of the 10 braking tests in the first decay test was obtained from the test results of Examples 7-17, Comparative Example 3, and Reference Example 1, and Δμ (maximum value - minimum value) was obtained from the difference between the maximum μ and the minimum μ in the first decay test. The results are shown in Tables 2 and 3 below.
[0185] [Table 2] [Table 3] (Friction Test 2) The surface (friction surface) of the friction component (low-iron component) was ground to 1.0 mm to form a friction component for multi-scale dynamic testing. This friction component and rotor (a type A cast iron rotor in the ASTM standard) were used at speeds of 65 km / h and 3.5 m / s². 2The friction components and rotor, which had been pre-broken in under the above conditions, were tested under the friction conditions listed in Table 4. The average coefficient of friction, wear of the friction material, and wear of the rotor were measured. The test was conducted twice, and the average of the two tests was taken as the measurement result. The results are shown in Table 5.
[0186] (Calculation of frictional dust) The surface (friction surface) of the friction component (low-iron component) was ground to 1.0 mm to form a friction component for multi-scale dynamic testing. This friction component and a disc rotor (a type A cast iron rotor in the ASTM standard) were used at speeds of 65 km / h and 3.5 m / s². 2 The friction dust collection device was broken in under 500 braking cycles and then connected to a multi-scale dynamic device. A TOKYO DYLEC MCI sampler (a filter for capturing PM10-2.5 and PM2.5) was installed on the friction dust collection device. Next, friction tests were conducted on the friction components and disc rotor, which had been broken in under the above conditions, under the friction conditions specified in Table 4. The mass of particulate matter (the amount of PM10-2.5 and PM2.5 generated during the friction test) collected by the filter was measured. The test was performed twice, and the average of the two measurements was taken as the result. The results are shown in Table 6.
[0187] [Table 4] [Table 5] [Table 6] Table 5 confirms that the friction components of Examples 18 to 21, which employ a pseudo-tunnel crystal structure of potassium magnesium titanate (titanium 1), can form low-iron materials with low wear of friction materials, rotors, etc.
[0188] On the other hand, the friction components of Comparative Examples 4 and 6, which only used titanate A with a layered crystal structure, and the friction components of Comparative Examples 5 and 7, which did not contain titanate, had unsatisfactory coefficients of friction.
[0189] Table 6 confirms that the friction components of Examples 18 and 9, which employ a pseudo-tunnel crystal structure of potassium magnesium titanate (titanium 1), can form low-iron components with less fine dust.
[0190] Furthermore, it was confirmed that the friction components of Examples 20 and 21, which contain potassium magnesium titanate (titanium 1) with a pseudo-tunnel crystal structure and do not contain tin sulfide, can form low-iron components with particularly low generation of fine dust.
[0191] On the other hand, the friction component of Comparative Example 5, which does not contain titanate, generates more fine dust, which is not ideal.
Claims
1. A magnesium potassium titanate, wherein, The magnesium potassium titanate is composed of the formula K x Mg 0.4 Ti 1.6 O 4-y This means that in the formula, x is 0.1 ≤ x ≤ 0.6, and y = (0.8 - x) / 2. In the Raman spectrum of the potassium magnesium titanate, 100 cm⁻¹ ﹣1 ~165cm ﹣1 The peak area (Ia) at 215 cm⁻¹ ﹣1 ~325cm ﹣1 The ratio of peak area (Ib) at 785 cm⁻¹ (Ia / Ib) is above 0.
03. ﹣1 ~900cm ﹣1 Peak area (Ic) at 215 cm⁻¹ ﹣1 ~325cm ﹣1 The ratio of peak area (Ib) at that point (Ic / Ib) is below 0.
40.
2. The magnesium potassium titanate as described in claim 1, characterized in that, The magnesium potassium titanate does not actually contain anatase titanium dioxide.
3. The magnesium potassium titanate as described in claim 1 or 2, characterized in that, The magnesium potassium titanate is in the form of plate-shaped particles.
4. The magnesium potassium titanate as described in claim 1 or 2, characterized in that, The average particle size of the magnesium potassium titanate is 0.1 μm to 100 μm.
5. The magnesium potassium titanate as described in claim 1 or 2, characterized in that, The specific surface area of the magnesium potassium titanate is 0.1 m². 2 / g~10m 2 / g.
6. The magnesium potassium titanate as described in claim 1 or 2, characterized in that, The alkali metal ion dissolution rate of the magnesium potassium titanate is 0.01% to 15% by mass.
7. A friction-modifying material, characterized in that, The friction modulating material comprises the magnesium potassium titanate as described in claim 1 or 2.
8. A friction material composition, characterized in that, The friction material composition contains the magnesium potassium titanate and the binding material as described in claim 1 or 2, and the copper component has a content of less than 0.5% by mass relative to 100% of the total mass of the friction material composition, calculated as copper element.
9. The friction material composition according to claim 8, characterized in that, The content of the magnesium potassium titanate relative to the total mass percentage of the friction material composition is 1% to 40% by mass.
10. The friction material composition according to claim 8, characterized in that, It also contains at least one of titanates with a layered crystal structure and titanates with a tunnel-like crystal structure.
11. The friction material composition according to claim 8, characterized in that, The friction material composition does not substantially contain sulfide-based solid lubricants.
12. The friction material composition according to claim 8, characterized in that, The content of steel-based fibers is less than 10% by mass relative to the total mass of the friction material composition (100% by mass).
13. The friction material composition as claimed in claim 8, characterized in that, The content of steel-based fibers relative to the total mass percentage of the friction material composition is 10% or more.
14. A friction material, characterized in that, The friction material is a molded body of the friction material composition according to claim 8.
15. A friction component, characterized in that, The friction component comprises the friction material as described in claim 14.
Citation Information
Patent Citations
Friction material composition, friction material, and friction member
WO2018164028A1